Global development finance building coalitions for effective development finance. Analysis and summary tables, 2001. (Washington, D.C. ; [Great Britain] World Bank, 2001)
This volume begins with an analysis of near term growth prospects in developing countries. The report examines in detail recent developments and prospects for private and public development finance.
Includes bibliographical references.
Keywords: Debts, External -- Developing countries; International finance; Investments, Foreign -- Developing countries; Developing countries -- Economic conditions